A quilt for Christmas - Dallas, Sandra (St. Martin's Press, 2014)
"It is 1864 and Eliza Spooner's husband Will has joined the Kansas volunteers to fight the Confederates, leaving her with their two children and in charge of their home and land. Eliza is confident that he will return home, and she helps pass the months making a special quilt to keep Will warm during his winter months in the army. When the unthinkable happens, she takes in a a woman and child who have been left alone and made vulnerable by the war, and she finds solace and camaraderie amongst the women of her quilting group. And when she is asked to help hide an escaped slave, she must decide for herself what is right, and who can she can count on to help her."--